The AI‐based AlphaFold 2 algorithm predicts an open structure for tauC3 - Chain, Daniel G; Margolin, Richard A (Alzheimer's & dementia, 2023)
Background TauC3 is an especially noxious C‐terminal tau fragment produced by caspase‐3 cleavage at Asp421. Two decades of accumulating evidence support its importance in the pathogenesis of AD and other tauopathies, notably FTD and PSP. TauC3 promotes aggregation and filament formation, recruits full length tau (FLT) to incipient fibrils, and despite low concentration in AD brain tissue relative to total tau, has been reported to account for substantially all the seeding activity in AD brain extracts. TauC3 has also been shown to slow fast axonal transport (FAT), with deleterious consequences. Although tau’s largely disordered structure prevents analysis by X‐ray crystallography, FRET analysis suggested the existence of a hairpin conformation in which the N‐terminus folds over the C‐terminus close to the MTBR. In this model, Ser432 is the point of closest contact with Pro301. Opening of the hairpin has been hypothesized to 1) make FLT prone to aggregation by exposing the MTBR, and 2) impair FAT by overexposing the phosphatase activating domain near the N‐terminus. We postulated that tauC3 cannot form the hairpin because it lacks Ser432 and thus has an “open” conformation. This would explain tauC3’s substantially increased pathogenicity compared to FLT. The AI‐based tool AlphaFold 2 (AF2) is being used to predict the conformation of many proteins with great accuracy. Applying it to FLT and tauC3 could provide valuable data about the hairpin and whether caspase cleavage alters it. Method We tested AF2’s ability to predict the conformation of 4‐repeat FLT and tauC3 from FASTA sequences, aligning the models produced with the MTBR. Result AF2 modeling revealed a dramatically different conformation for tauC3 compared to FLT, specifically, an open conformation with the MTBR and N‐terminus far apart (Figure). Interestingly, it also revealed that the entire C‐terminus region of FLT starting at Gln423 is composed of a single α‐helix. Conclusion AF2 predictions support the existence of the hairpin conformation for tau and underscore the critical importance of residue 432 in maintaining it. The extended C‐terminus α‐helix may have functional implications. TauC3’s open conformation is consistent with its slowing of FAT and its ability to seed aggregation even at low concentrations.